d) 2x^3 + 2x + x^2 + 1 = 0
2x(x^2 +1) + (x^2 +1)=0
(2x + 1)(x^2 +1)=0
=> 2x + 1 = 0 hoặc x^2 + 1 =0
=> 2x = -1 hoặc x^2 = -1
=> x = -1/2 hoặc x^2 = -1
Mà x^2>=0 => x = -1/2
e) 7x^2 - 16x = 2x^3 - 56
7x^2 - 16x - 2x^3 + 56 = 0
7x^2 - 2x^3 - 16x + 56 = 0
x^2(7-2x) - 8(2x-7) = 0
x^2(7-2x) + 8(7-2x) = 0
(x^2 +8)(7-2x)=0
=> x^2 + 8 = 0 hoẵ 7 - 2 x= 0
=> x^2 = -8 hoặc 2x = 7
=> x^2=-8 hoặc x = 7/2
Mà x^2>=0
=> x = 7/2
f) x^3 - 19x - 30 = 0
x^3 - 3x^2 + 3x^2 - 10x - 9x - 30=0
x^3 - 3x^2-10x + 3x^2 - 9x - 30 =0
x(x^2-3x-10) + 3(x^2 - 3x - 10)=0
(x+3)(x^2-3x-10)=0
(x+3)(x^2 + 2x - 5x - 10)=0
(x+3)[x(x+2) - 5(x+2)]=0
(x+3)(x+2)(x-5)=0
=> x = -3 hoặc x = -2 hoặc x = 5
g) x^3 + 4x^2 - 7x - 10 = 0
x^3-x^2-2x+5x^2-5x-10=0
x(x^2 - x - 2) + 5(x^2 - x -2)=0
(x+5)(x^2-x-2)=0
(x+5)(x^2 - 2x + x -2)=0
(x+5)[x(x-2) + (x-2)]=0
(x+5)(x+1)(x-2)=0
=> x = -5 hoặc x = 2 hoặc x =-1